2014
DOI: 10.1016/j.jhep.2013.08.024
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor SALL4 regulates stemness of EpCAM-positive hepatocellular carcinoma

Abstract: Background & Aims: Recent evidence suggests that hepatocellular carcinoma can be classified into certain molecular subtypes with distinct prognoses based on the stem/maturational status of the tumor. We investigated the transcription program deregulated in hepatocellular carcinomas with stem cell features. Methods: Gene and protein expression profiles were obtained from 238 (analyzed by microarray), 144 (analyzed by immunohistochemistry), and 61 (analyzed by qRT-PCR) hepatocellular carcinoma cases. Activation/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 39 publications
12
127
0
Order By: Relevance
“…We recently demonstrated that HDACs are activated in EpCAM + HCCs, and that HDAC inhibitors successfully inhibit the growth of EpCAM + HCC cell lines [18]. We evaluated the expression of HDAC1 in 38 surgically resected snap-frozen specimens using qRT-PCR.…”
Section: Overcoming Epcam + Hcc By Targeting Chd4 Through Hdac/parp Imentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that HDACs are activated in EpCAM + HCCs, and that HDAC inhibitors successfully inhibit the growth of EpCAM + HCC cell lines [18]. We evaluated the expression of HDAC1 in 38 surgically resected snap-frozen specimens using qRT-PCR.…”
Section: Overcoming Epcam + Hcc By Targeting Chd4 Through Hdac/parp Imentioning
confidence: 99%
“…It has been reported by three independent groups that SALL4 is a biomarker of HCCs with stem-like gene expression signatures and a poor prognosis [18,25,26]. SALL4 was recently found to directly interact with the epigenetic modulator nucleosome remodeling and histone deacetylase (NuRD) complex [27], thereby altering the histone modifications associated with stemness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Others regard SALL4 to be a marker of liver CSCs, which can be used to predict HCC treatment outcomes. [40][41][42] Furthermore, expression of phosphatase and tensin homologue protein was suppressed and the formation of tumors in xenograft models was inhibited by overexpression of SALL4. 43 Thus, inhibiting expression of SALL4 can inhibit proliferation and differentiation of liver cancer cells.…”
Section: Obtaining Hepatic Cscsmentioning
confidence: 99%
“…Zebularine, a DNA methyltransferase (DNMT) inhibitor, declined CSC properties such as self-renewal and tumor-initiating capacities in HCC cells [43]. Histone deacetylase (HDAC) inhibitors such as trichostatin A and vorinostat have been shown to preferentially suppress the cell growth of SALL4-overexpressing HCC cell lines compared with that of SALL4 − HCC cell lines [44,45]. These indings suggest that epigenetic therapy using DNMT inhibitors and/ or HDAC inhibitors may be a promising approach for the eradication of CSCs in HCC.…”
Section: Therapy For Hccmentioning
confidence: 99%